2018
DOI: 10.1521/soco.2018.36.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Grandiose Narcissists Seek Status Selectively

Abstract: Grandiose narcissists (individuals with a tendency to be self-focused, egotistical, and vain) overwhelmingly desire celebrity status. Here, we examined the conditions underlying narcissists' fame motivation. In Study 1, we assessed participants' desire to become a social media user who attained high status, tried to attain status but failed, or had no status-attainment goal. In Study 2, we assessed how participants' self-perceived similarity to high-status targets (e.g., Hollywood/social media celebrities) inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(69 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, power over others allows them to engage in favorable situations to improve their social status. These findings are in line with past studies that indicated that grandiose narcissists have a strong need for power and strategically seek status (Giacomin, Battaglini & Rule, 2018;Zeigler-Hill, McCabe, Vrabel, Raby & Cronin, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, power over others allows them to engage in favorable situations to improve their social status. These findings are in line with past studies that indicated that grandiose narcissists have a strong need for power and strategically seek status (Giacomin, Battaglini & Rule, 2018;Zeigler-Hill, McCabe, Vrabel, Raby & Cronin, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The discrepancy could be explained by status differences between employees and their supervisors, and suggests that narcissistic employees are more motivated to hide their negative side from their supervisor than their peers. Narcissistic individuals' sensitivity to the status of others (Giacomin et al., 2018 ; Horton & Sedikides, 2009 ) leads them to seek social alliances with people that they perceive as having high status (Buss & Chido, 1991 ; Jonason & Schmitt, 2012 ) and to solicit their approval (Ashton‐James & Levordashka, 2013 ). As such, peers may be better positioned to detect the negative aspects of narcissistic employees than the supervisor.…”
Section: Discussionmentioning
confidence: 99%
“…Narcissistic individuals' need to impress high‐status others (Giacomin et al., 2018 ), coupled with their desire to ascend formal hierarchies (Zitek & Jordan, 2016 ), implies that narcissistic employees will be particularly motivated to use impression management tactics to present themselves favorably to their supervisors. One such tactic, self‐promotion, is aimed at highlighting one's competencies and involves taking credit for positive events, making others aware of one's accomplishments, and emphasizing one's performances (Bolino et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%